2015
DOI: 10.4110/in.2015.15.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Protection AgainstSalmonellaTyphimurium,SalmonellaGallinarum, andSalmonellaEnteritidis Infection in Layer Chickens Conferred by a Live AttenuatedSalmonellaTyphimurium Strain

Abstract: In the present study, we investigated the protection conferred by a live attenuated Salmonella enterica serovar Typhimurium (ST) strain against Salmonella Typhimurium, Salmonella Gallinarum (SG), and Salmonella Enteritidis (SE) infection in layer chickens. Birds were orally primed with the attenuated ST strain at 7 days of age and then boosted at 4 weeks post prime immunization (PPI). Sequential monitoring of plasma IgG and mucosal secretory IgA (sIgA) levels revealed that inoculation with ST induced a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…CS(OMP+FLA)-based vaccines induced higher antibody and/or cellular immune responses, correlated with improved protective efficiency, but the commercial vaccine did not induce any such substantial immune response, suggesting the need for further studies to understand its mechanism of induction of protection in broilers. However, the commercial live vaccine stimulated significant levels of specific IgG and IgA responses in layer birds [ 41 ]. This may be due to the age difference between broilers and layers at the time of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…CS(OMP+FLA)-based vaccines induced higher antibody and/or cellular immune responses, correlated with improved protective efficiency, but the commercial vaccine did not induce any such substantial immune response, suggesting the need for further studies to understand its mechanism of induction of protection in broilers. However, the commercial live vaccine stimulated significant levels of specific IgG and IgA responses in layer birds [ 41 ]. This may be due to the age difference between broilers and layers at the time of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, live Salmonella vaccines were reported to induce cross-immunity against related serovars (MATULOVA et al, 2013;MOHLER et al, 2008). Although ST infection is common in chickens, it does not cause severe disease in poultry (CHAPPELL et al, 2009); consequently, attenuated ST strains have been used successfully to express foreign antigens and have been suggested as safe strains (LEE, 2015). In this study, administering a ST vaccine did not induce mortality or any adverse effects in the vaccinated birds.…”
Section: Discussionmentioning
confidence: 49%
“…In recent years, the use of genetically modified S. Typhimurium (ST) strains as immunization agents has gained remarkable popularity, since these strains have no clinical side effects (CHAUDHARI; LEE, 2013) and may provide some protection against other serovars (LEE, 2015). According with HUANG et al, (2016), an attenuated ST vaccine strain has shown to offer protection against S. Enteritidis virulent challenge in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella vaccines can also offer inter-serotypic cross immunity. For example, a study showed that layer chickens are protected against Salmonella typhimurium , S. gallinarum , and S. enteritidis infections when given a live attenuated Salmonella enterica serovar typhimurium strain at 7 days of age followed by boosting at 5 weeks of age [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variable morbidity and mortality rates in chickens infected with S. gallinarum have been reported in earlier studies depending on the age and immune status of the birds, virulence of the bacterial strains, management status, rearing system, biosecurity measures, etc. For example, the S. gallinarum produces very high mortality (40%–100%) in chicks with severe inflammation in the liver and spleen [ 29 , 31 , 32 ]. However, the mortality rates of S. gallinarum infection in layer chickens varied greatly between studies.…”
Section: Discussionmentioning
confidence: 99%